Analysis of the Implementation of the Merdeka Curriculum Using the Pedagogical Deep Learning Approach in a Bilingual Primary School Based on the CIPP Evaluation Model - Lenny Lenny; Zulela MS; Muhammad Afandi; Vina Iasha (PT. Intelektiva Global Nusantara, 2026)
This study examines the implementation of the Merdeka Curriculum through a pedagogical deep learning approach, referring to meaningful and student-centered learning rather than artificial intelligence, in a bilingual elementary school. A qualitative evaluation was conducted using the CIPP (Context, Input, Process, Product) model. Data were collected through observations, interviews, and document analysis. The findings show that the curriculum aligns with the school's vision and students' needs. Although learning is active and contextual, some teachers require stronger pedagogical competence due to non-linear educational backgrounds, and higher-order thinking practices remain inconsistent. The curriculum positively supports student engagement, character development, and critical thinking. This study contributes practical evidence on implementing the Merdeka Curriculum in bilingual elementary schools and highlights continuous teacher professional development as a key factor for strengthening pedagogical deep learning.